Results of a three-year observation of the course of non-radiological axial spondyloarthritis - Yu. Yu. Grabovetskaya; A. V. Smirnov; M. V. Cherkasova; A. A. Rudneva; A. M. Lila (Современная ревматология, 2024)
Identification of the non-radiological stage of axial spondyloarthritis (nr-axSpA) has contributed to the improvement of diagnostics and the expansion of therapeutic approaches in the early stages of the disease. However, there is still an unmet need for effective treatment of patients with active nr-axSpA.Objective: to evaluate the dynamics of nr-axSpA in patients in the Kaliningrad region and to identify additional factors influencing the radiological progression of the disease.Material and methods. A total of 68 patients with nr-axSpA were examined at baseline and during 3 year follow-up, most of them were women (62%). The median age of the participants was 27.5 [23.0; 33.3] years. The duration of diagnosis was 1 [1; 2] years. HLA-B27 antigen positivity was present in 40% of cases. Patients at baseline and during follow-up underwent a standard clinical and laboratory examination, pelvic radiography and magnetic resonance imaging of the sacroiliac joints. In addition, cytokine levels (visfatin, PPM1A, MIF, serum calprotectin) and the concentration of IgCD74 antibodies were determined.Results and discussion. After 3 years of follow-up, the diagnosis still met the criteria for nr-axSpA in 30 (44.1%) of the 68 patients, in 16 (23.5%) it transformed into radiographic axSpA (r-axSpA), in 7 (10.3%) – to axial psoriatic arthritis, in 13 (19.1%) the clinical picture no longer met the criteria for nr-axSpA, 2 (3%) patients dropped out of the study. When analyzing the values of visfatin, PPM1A, MIF and serum calprotectin, no differences were found between nr-axSpA and r-axSpA, while the average concentrations of IgCD74 antibodies were slightly higher in patients with nr-axSpA (7.4 and 5.0 ng/ml respectively). It was shown that the probability of radiological progression from nr-axSpA to r-axSpA increased 3.308-fold with a one-unit increase in the ASDAS (Ankylosing Spondylitis Disease Activity Score) index.Conclusion. The median duration of nr-axSpA diagnostics in the Kaliningrad region was 1 year. In terms of dynamics, after 3 years of observation, 44.1% of patients still met the criteria for nr-axSpA, and radiological progression to r-axSpA was observed in 23.5% of cases. High values of the ASDAS index and its increase by 1 unit increased the speed of radiological progression of nr-axSpA by 3.308 times. The difficulties in the early diagnosis of axSpA in practice necessitate the establishment of reference centers to obtain expert opinions on issues of differential diagnosis and treatment choices in patients with nr-axSpA and ankylosing spondylitis.